Development of a Web-Based Korean Triage and Acuity Scale Learning Program for Emergency Department Nurses. Issue 11 (12th November 2021) - Kim, Hyo-Jin; Kang, Hee-Young; Kim, Hae-Ran
Abstract : The Korean Triage and Acuity Scale is a tool developed to classify severity and urgency of emergency department patients, focusing on their symptoms. Considering the importance of the Korean Triage and Acuity Scale, learning for emergency department nurses who perform the Korean Triage and Acuity Scale must be structured to ensure that the knowledge they gain can be applied to various clinical situations of the emergency department. Moreover, Web-based learning is considered appropriate in this situation. This is a methodological research study that was conducted to develop a Web-based Korean Triage and Acuity Scale learning program for emergency department nurses. The learning program was developed using each of the five phases of the "analysis, design, development, implementation, and evaluation" model, that is, analysis, design, development, implementation, and evaluation. The learning program was composed of 22 cases of emergency situations based on the Korean Triage and Acuity Scale teaching material with an approval from the Korean Triage and Acuity Scale committee in the Korean Society of Emergency Medicine. The developed program was delivered in 4-hour sessions over 4 weeks. Emergency department nurses who were given the Web-based Korean Triage and Acuity Scale learning program showed improvement in work-site transfer and reported satisfactory learning. The findings indicate that the Web-based learning program for nurses can be used as an effective tool that is easily accessible and provides multiple learning opportunities.